El efecto de la satisfacción y el apego a la marca en la fidelidad del consumidor: Aplicación de la técnica PLS-SEM; The effect of satisfaction and brand attachment on consumer loyalty: Application of the PLS-SEM technique - Omar Boubker; Abdellah Aatar (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– Today, improving brand loyalty is an important focus for organizations. However, one way to achieve this is to improve consumer satisfaction and brand attachment. Thus, the purpose of this study is to explore the effects of consumer satisfaction and emotional brand attachment on brand loyalty. For this purpose, we adopted the partial least squares structural equation modeling (PLS-SEM) approach. The data were collected by means of a self-administered online questionnaire from a sample of 210 consumers of a brand of dairy products. The findings confirm the influence of consumer satisfaction and emotional brand attachment. This study suggests marketing solutions facilitating consumer brand loyalty policy, especially in the dairy industry.
Keywords: C5; C12; C83; M31; 330; Brand loyalty; preference; attitude; satisfaction